Polycyclic aromatic compounds in the Canadian Environment: Aquatic and terrestrial environments. (15th September 2021) - Marvin, Christopher H.; Berthiaume, Alicia; Burniston, Deborah A.; Chibwe, Leah; Dove, Alice; Evans, Marlene; Hewitt, L. Mark; Hodson, Peter V.; Muir, Derek C.G.; Parrott, Joanne; Thomas, Philippe J.; Tomy, Gregg T.
Abstract: Polycyclic aromatic compounds (PACs) are ubiquitous across environmental media in Canada, including surface water, soil, sediment and snowpack. Information is presented according to pan-Canadian sources, and key geographical areas including the Great Lakes, the Alberta Oil Sands Region (AOSR) and the Canadian Arctic. Significant PAC releases result from exploitation of fossil fuels containing naturally-derived PACs, with anthropogenic sources related to production, upgrading and transport which also release alkylated PACs. Continued expansion of the oil and gas industry indicates contamination by PACs may increase. Monitoring networks should be expanded, and include petrogenic PACs in their analytical schema, particularly near fuel transportation routes. National-scale roll-ups of emission budgets may not expose important details for localized areas, and on local scales emissions can be substantial without significantly contributing to total Canadian emissions. Burning organic matter produces mainly parent or pyrogenic PACs, with forest fires and coal combustion to produce iron and steel being major sources of pyrogenic PACs in Canada. Another major source is the use of carbon electrodes at aluminum smelters in British Columbia and Quebec. Temporal trends in PAC levels across the Great Lakes basin have remained relatively consistent over the past four decades. Management actions to reduce PAC loadings have been countered by increased urbanization, vehicular emissions and areas of impervious surfaces. Major cities within the Great Lakes watershed act as diffuse sources of PACs, and result in coronas of contamination emanating from urban centres, highlighting the need for non-point source controls to reduce loadings. Highlights: Urban centres within the Great Lakes watershed act as diffuse sources of PACs. National roll-ups of emission budgets may not expose details for localized areas. Expansion of the oil and gas industry indicates contamination by PACs may increase. Coal combustion to produce aluminum and steel is a large source of pyrogenic PACs. Oil recovery produces mainly alkylated PACs, while burning organic matter produces parent PACs.